Multimodal Practice for Mobilizing Response: The Case of Turn-Final Tu Vois ‘You See’ in French Talk-in-Interaction - Stoenica, Ioana-Maria; Fiedler, Sophia (Frontiers in Psychology, 2021)
One of the most frequent verbal expressions that people use when interacting with each other in French is tu vois ‘you see’ (Cappeau 2004). Drawing on interactional linguistics and multimodal analysis, we examine the interactional functioning of this verbal expression when occurring in turn-final position. Previous studies on tu vois ‘you see’ in this position document only its use for marking the end of an utterance or for turn-yielding. The following aspects have thus far remained unexplored: The interactional environment in which the construction occurs, how it is connected to the speaker’s embodied conduct, the way in which it contributes to mobilizing a response from the recipient, as well as the nature of this response. Our paper addresses these issues and shows that turn-final tu vois ‘you see’ is systematically produced with a final rising intonation and coupled with the speaker’s gaze directed to the recipient. This multimodal practice is recurrently deployed in turns conveying the speaker’s emotional stance, in turns performing a dispreferred action, like disagreeing, and in turns claiming insufficient knowledge. The response that is invited using this multimodal practice is distinctly tailored to each of these actions: an affiliative response, an aligning response, and a response addressing the prior speaker’s claim of insufficient knowledge from the recipient’s own point of view. By presenting an in-depth study of the action sequences in which tu vois ‘you see’ is employed, as well as of its multimodal packaging, this contribution highlights the prospective, i.e. response-mobilizing potential of this interactional resource and shows that its use entails sequential implications even when it accompanies actions that project only weakly a response from the recipient.